A Rough Set-Based Approach for Identifying and Replacing Missing Concepts in Incomplete Sentences in Computer Domain Texts - Nur Faiqah ‘Aqilah binti Fuaad (Universiti Sains Islam Malaysia, 2026)
Matric: 3202504 (FST)